2011
DOI: 10.1007/s00421-011-1888-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-day vitamin E supplementation on muscle injury after downhill running in rats

Abstract: Antioxidant supplementation has been suggested to prevent exercise-induced muscle injury, but the findings are inconsistent. The objective of this study was to investigate the potential protective role of vitamin E treatment against eccentric exercise-induced muscle injury by examining morphological and functional alterations in rat soleus muscle after downhill running as well as muscle injury markers in the blood. Sixty adult male Wistar rats were randomly assigned to vitamin E-treated or placebo-treated grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…Despite the progress of analytic techniques and the refinement of study designs, striking disagreement exists among studies regarding the influence of antioxidant supplementation on physical performance and redox homeostasis. Indeed, several studies have indicated that antioxidant supplementation induces a positive effect (Jakeman and Maxwell, 1993;Shafat et al, 2004), a negative effect (Gomez-Cabrera et al, 2008;Ristow et al, 2009) or no effect (Yfanti et al, 2010;Kyparos et al, 2011;Theodorou et al, 2011) on muscle performance. Likewise, several studies have reported that antioxidant supplementation attenuates oxidative stress (Close et al, 2006;Kinnunen et al, 2009), others have reported that it induces a pro-oxidant effect (McAnulty et al, 2005;Versari et al, 2006) and others have reported that it does not affect redox homeostasis (Rytter et al, 2010;Theodorou et al, 2011).…”
Section: Possible Biological Importance Of Exercise-induced Alteratiomentioning
confidence: 99%
“…Despite the progress of analytic techniques and the refinement of study designs, striking disagreement exists among studies regarding the influence of antioxidant supplementation on physical performance and redox homeostasis. Indeed, several studies have indicated that antioxidant supplementation induces a positive effect (Jakeman and Maxwell, 1993;Shafat et al, 2004), a negative effect (Gomez-Cabrera et al, 2008;Ristow et al, 2009) or no effect (Yfanti et al, 2010;Kyparos et al, 2011;Theodorou et al, 2011) on muscle performance. Likewise, several studies have reported that antioxidant supplementation attenuates oxidative stress (Close et al, 2006;Kinnunen et al, 2009), others have reported that it induces a pro-oxidant effect (McAnulty et al, 2005;Versari et al, 2006) and others have reported that it does not affect redox homeostasis (Rytter et al, 2010;Theodorou et al, 2011).…”
Section: Possible Biological Importance Of Exercise-induced Alteratiomentioning
confidence: 99%
“…The relatively little data available from human [2731] and animal [3234] studies have failed to show consistently any protective effect of vitamin E on muscle force deficit caused by eccentric contraction-biased exercise. Only in the study of Shafat et al [35], in which though a combination of vitamins E and C was administered, attenuation of the force decline following eccentric exercise in the supplemented group was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been recently demonstrated in vitamin-E-supplemented rats that, even though maximal isometric tetanic force ( P o ) was not clearly spared following eccentric contraction-biased exercise, single twitch force ( P t ), which reflects Ca 2+ kinetics in the muscle [36], declined significantly less compared to the placebo conditions [32]. Based on this evidence, we hypothesized that any potential effect of vitamin E treatment to attenuate muscle injury-induced force decline could be better tested by utilizing a low-frequency stimulation protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For rodents, this is a potent stressor 10,11 . Other types of models force the animals to run in treadmills [12][13][14] , using electric shocks 15,16 or brushes 17 to motivate them. An extensive literature search did not find experiments utilizing grouped animals and adding their combined activity to assess exercise performance or propensity that could be used to compare in animals, point by point, the seven conclusions derived by the International Society of Sports Nutrition from humans 18 .…”
mentioning
confidence: 99%